2005
DOI: 10.1590/s0100-879x2005000100015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the GABA B agonist baclofen on dipyrone-induced delayed gastric emptying in rats

Abstract: Dipyrone administered intravenously (iv) or intracerebroventricularly (icv) delays gastric emptying (GE) in rats. Gamma-aminobutyric acid (GABA) is the most potent inhibitory neurotransmitter of the central nervous system. The objective of the present study was to determine the effect of icv baclofen, a GABA B receptor agonist, on delayed GE induced by dipyrone. Adult male Wistar rats received a saline test meal containing phenol red as a marker. GE was indirectly evaluated by determining the percent of gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Additionally, it was demonstrated that the delay in GE determined by AA was blocked by the administration of bac in the CNS ( Figure 4B), as also reported for Dp (2). In the CNS, bac activates GABA B receptors, promoting modulation of neurotransmission by hyperpolarization of the postsynaptic membranes or inhibition of neurotransmitter release at the presynaptic endings (18).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Additionally, it was demonstrated that the delay in GE determined by AA was blocked by the administration of bac in the CNS ( Figure 4B), as also reported for Dp (2). In the CNS, bac activates GABA B receptors, promoting modulation of neurotransmission by hyperpolarization of the postsynaptic membranes or inhibition of neurotransmitter release at the presynaptic endings (18).…”
Section: Discussionsupporting
confidence: 78%
“…Dp (Sigma, St. Louis, MO, USA), AA (Sigma) and bac (Sigma) were diluted with sterile physiological saline as a vehicle at the time of the study. The doses, in µmol, applied iv and icv were established on the basis of previous studies with Dp (1,2). GE and stomach compliance were determined after a 24-h fast, although the animals continued to receive water ad libitum up to 30 min before the studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of injury has been selected because most of the NI children referred for antireflux surgery have either experienced perinatal hypoxic problems or have been victims of near-drowning 2 . Also, this is a well established experimental model that has been widely employed to study many different aspects of neurological diseases [11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…GE was estimated indirectly by measuring percent gastric retention (%GR) of a saline test meal according to the method of Collares et al 12 as following. Every procedure was undertaken after a 22-hour fast.…”
Section: Evaluation Of Gastric Emptyingmentioning
confidence: 99%